Mechanism of Bone-metastatic LUAD Cells Promoting Angiogenesis Through HGF/YAP Signaling Pathway - Yan DENG; Rong QIU; Xingyu LIU; Yingyang SU; Yang XUE; Yuzhen DU (Chinese Journal of Lung Cancer)
Background and objective The early stages of tumor bone metastasis are closely associated with changes in the vascular niche of the bone microenvironment, and abnormal angiogenesis accelerates tumor metastasis and progression. However, the effects of lung adenocarcinoma (LUAD) cells reprogrammed by the bone microenvironment on the vascular niche within the bone microenvironment and the underlying mechanisms remain unclear. This study investigates the effects and mechanisms of LUAD cells reprogrammed by the bone microenvironment on endothelial cells and angiogenesis, providing insights into the influence of tumor cells on the vascular niche within the bone microenvironment. Methods The culture media from bone-metastatic LUAD cell A549-GFP-LUC-BM3 (BM3-CM) and A549-GFP-LUC (A549-CM) were separately applied to human umbilical vein endothelial cell (HUVEC). A colony formation assay, scratch assay, and tube formation assay were conducted to evaluate the proliferation, migration, and angiogenesis of HUVEC. Gene set enrichment analysis (GSEA) was conducted to identify enriched pathways, while reverse transcription quantitative polymerase chain reaction (RT-qPCR) and enzyme linked immunosorbent assay (ELISA) were performed to quantify hepatocyte growth factor (HGF), a protein that plays a crucial role in angiogenesis. Furthermore, the pivotal function of HGF and its underlying molecular mechanisms have been substantiated through the utilisation of recombinant proteins, neutralising antibodies, pathway inhibitors, immunofluorescence staining, and Western blot. Results BM3-CM demonstrated a more pronounced impact on the proliferation, migration, and angiogenesis of HUVEC compared to A549-CM. Bioinformatics analysis, combined with in vitro experiment, demonstrated that the secretory protein HGF was significantly elevated in BM3 cells and BM3-CM (P<0.05). The addition of HGF neutralizing antibodies to BM3-CM inhibited the promoting effect of BM3-CM on HUVEC (P<0.05), while the addition of recombinant HGF to A549-CM reproduced that promoting effect of BM3-CM on HUVEC (P<0.05). HGF can enhance the activation of YAP (Yes-associated protein) in HUVEC, and this promotion effect may be achieved by activating Src and activating YAP into the nucleus (P<0.05), but this effect can be inhibited by HGF neutralizing antibodies (P<0.05). Furthermore, the addition of recombinant HGF to A549-CM can recapitulate the YAP activation effect of BM3-CM in HUVEC (P<0.05). Conclusion Bone microenvironment reprogrammed bone-metastatic LUAD cells BM3 promote the proliferation, migration, and angiogenesis of HUVEC through the HGF/YAP axis, potentially playing a significant role in the modifications of the vascular niche.